2018
DOI: 10.1200/jco.2017.77.0412
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-Up of Nivolumab in Previously Treated Advanced Non–Small-Cell Lung Cancer: Results From the CA209-003 Study

Abstract: Purpose In two phase III studies, nivolumab, a programmed death-1 (PD-1) inhibitor antibody, improved overall survival (OS) versus docetaxel in pretreated advanced non-small-cell lung cancer (NSCLC). We report 5-year follow-up results from an early phase I study of nivolumab in this patient population and describe characteristics of 5-year survivors. Patients and Methods Patients with pretreated, advanced NSCLC received nivolumab 1, 3, or 10 mg/kg every 2 weeks in 8-week cycles for up to 96 weeks. OS from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
509
2
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 605 publications
(544 citation statements)
references
References 18 publications
21
509
2
12
Order By: Relevance
“…The phase 1/2 open‐label CheckMate 077 study investigated the use of nivolumab, including 3 mg/kg and 240 mg Q2W, in Chinese patients with previously treated advanced or recurrent solid tumors, comprising NSCLC, hepatocellular carcinoma, and nasopharyngeal carcinoma (NPC) . In this study, nivolumab was well tolerated, and its pharmacokinetic (PK) profile in Chinese patients was similar to that previously reported in a US population . The open‐label, randomized, phase 3 CheckMate 078 study evaluated nivolumab 3 mg/kg Q2W versus docetaxel 75 mg/m 2 every 3 weeks in a predominantly Chinese patient population with advanced or metastatic NSCLC (squamous or nonsquamous) and disease progression during or after 1 prior platinum‐based doublet chemotherapy regimen.…”
supporting
confidence: 67%
“…The phase 1/2 open‐label CheckMate 077 study investigated the use of nivolumab, including 3 mg/kg and 240 mg Q2W, in Chinese patients with previously treated advanced or recurrent solid tumors, comprising NSCLC, hepatocellular carcinoma, and nasopharyngeal carcinoma (NPC) . In this study, nivolumab was well tolerated, and its pharmacokinetic (PK) profile in Chinese patients was similar to that previously reported in a US population . The open‐label, randomized, phase 3 CheckMate 078 study evaluated nivolumab 3 mg/kg Q2W versus docetaxel 75 mg/m 2 every 3 weeks in a predominantly Chinese patient population with advanced or metastatic NSCLC (squamous or nonsquamous) and disease progression during or after 1 prior platinum‐based doublet chemotherapy regimen.…”
supporting
confidence: 67%
“…The latest articles and abstracts published in the 2018 ASCO annual meeting have reported a series of recent results on the advances of immune checkpoint inhibitors in lung cancer. Focusing on immune checkpoint inhibitor monotherapy, 5‐year follow‐up results from the CA209‐003 study ( n = 129) showed promising long‐term OS and durable responses in a proportion of patients with pretreated advanced NSCLC receiving nivolumab treatment . The estimated 5‐year OS rate was 16% for all nivolumab‐treated patients.…”
Section: Advances In Immunotherapy In Chinamentioning
confidence: 99%
“…2 Significant advances during the last years were the advent of targeted therapies, i.e. 4 Identification of NSCLC patients likely to profit from these novel therapies relies on the detection of specific biomarkers in tumor biopsies. 4 Identification of NSCLC patients likely to profit from these novel therapies relies on the detection of specific biomarkers in tumor biopsies.…”
Section: Introductionmentioning
confidence: 99%